The Role of Metal Species on Aldehyde Hydrogenation over Co13 and Ni13 Supported on γ-Al2O3(110) Surfaces: A Theoretical Study - Rusrina Salaeh (2020)
© 2020 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim Fatty acid transformation to alkane in biomass conversion process goes through deoxygenation (DO) reaction with two possible pathways of hydrodeoxygenation (HDO) or decarbonylation (DCO) that yield different alkane products and water or CO as by-products. The favorability of aldehyde hydrogenation step can lead to HDO route rather than DCO route. The Co/γ-Al2O3 catalyst was previously observed experimentally to promote HDO and DCO routes while mostly DCO route was promoted on Ni/γ-Al2O3 catalyst. This work, we performed density functional theory (DFT) calculations to understand the role of metal species Co and Ni supported on γ-Al2O3 on aldehyde hydrogenation which could lead to the occurrence of HDO. The structural and electronic properties of supported Co13 and Ni13 clusters on γ-Al2O3 were examined. The perimeter site between the metal cluster and Al atom of γ-Al2O3 support is found to be an active site on both catalysts. The calculations suggest that Co13/γ-Al2O3 is more kinetically and thermodynamically favorable for acetaldehyde hydrogenation than Ni13/γ-Al2O3. The metal clusters also act as active sites for H2 dissociation. The supported Co13 cluster is oxidized at a higher degree results in higher negative charges of dissociated H2 while those on supported Ni13 shows heterolytic cleavage of H2 yielding both positive and negative hydrogen charges. This behavior could facilitate lower energy barrier of hydrogenation observed on Co13/γ-Al2O3 catalyst.